Ultrasound influence on coleoptile length at Poaceae seedlings as valuable criteria in prebreeding and breeding processes - Kratovalieva, Suzana; Srbinoska, Marija; Popsimonova, Gordana; Selamovska, Ana; Meglic, Vladimir; Andjelkovic, Violeta (National Library of Serbia, 2012)
The study includes research on the effect of ultrasound on the ability of seed germination and coleoptile development of cereal landraces (fam. Poaceae): oat (Avena sativa L.) brodski, rye (Secale cereale L.) rakotinska, Triticale svetinikolsko and soft wheat (Triticum aestivum L.) govrlevska. The experiment with ultrasound was carried out at frequency of 30-40 kHz on the thermostatic ultrasonic bath. Seeds were sonicated at a constant temperature (25?C) for 15 min. Ultrasound effect is reflected in the length of the coleoptyl and mesocotyl, although in a good deal is genetically predetermined. Coleoptile length was the longest in Triticale (3.3-5.5 cm) and approximately the same lengths are evident in rye (3.0-6.1 cm). Concerning the mesocotyl the longest one (5.525 cm ? 0.697) is recorded at rye, even significantly longer than control of oat and Triticale. Longer coleoptile of sonicated seeds indicates faster seedling development, good water supply and rapid development and emergence of first leaves. Correlation coefficient showed very high (0.821) and high R2 (67,472%) dependence among variables both, in length of coleoptiles (as dependent variable) and mesocotyl (as independent) with low standard error (0.225). With the simple use of ultrasound the germination period could be shorten, water supply more efficient, the sowing periods will be shorten and good yields even under conditions of climate change with increased temperatures could be achieved.